MODEL LOG-LINIER G2 PADA OBSERVASI TRIVARIAT LENGKAP - SANTIYASA, I WAYAN (Jurnal Matematika; Vol. 1, No. 1 April 2007DO - 10.24843/JMAT.2007.v01.i01.p03)
The log-linear models are most used to catagorical data analysis. The catagorical scale is the function transformation value form forth scale measured of observation : nominal, ordinal, ratio and interval. For the data analysis to trivariates observation of categorical scale is focus to create the models with proof for interaction the factor in the models to 2-factor or 3-factor with goodness-of-fit-test by G2 models.
Keywords: Catagorical scale, Log-Linear Models, Goodness of fit, G2 Models.